Extraction, Purification and Characterization of Poly Phenol Oxidase from Potato and Apple and Inhibition of Enzymatic Browning - Alneamah, Sadiq Jaafir Aziz; Aldhalemi, Ammar Abdulhasan Jaafar; Jannah, Salah Mahdi Al; Aldhalemi, Murtadha Abdulhasan Jaafar; Al-Obaidi, Laith Fareed Hasan (South Eastern European Journal of Public Health, 2024)
The purpose of this study was to determine the optimum conditions for the extraction of polyphenol oxidase (PPO) from potato and apple. PPO is found in a variety of fruits and vegetables and is the enzyme that causes browning reactions when handling damaged cells. At 405 nm, the enzyme activity was determined using spectrophotometry. PPO was researched to stop potato and apple from browning, which reduces their marketability. The outcomes showed that using an extraction buffer containing phosphate buffer (0.05 M, pH 6.6) was the optimum condition for the extraction of polyphenol oxidase from potato and apple. In addition, the results showed that as the temperature increased, the (PPO) activity increased, and the activity reached its peak at a temperature of 35 ͦC. The optimum pH value of (PPO) activity was 6.5 and we observed during the research that (PPO) decreased in strong acid condition and alkaline environments. Moreover, the results showed that the highest activity of polyphenol oxidase enzyme extracted from apple and potato was by using (O-dihydroxybenzene) as a substrate. As the concentration of the substrate increased, the (PPO) activity increased, reaching the optimum substrate concentration of 0.8%, and then its activity decreased. Also, we found that when using ascorbic acid, citric acid, and Na2SO3 as inhibitors, the activity of the polyphenol oxidase enzyme decreased with an increase in the concentration of ascorbic acid, citric acid, and Na2SO3. Sodium thiosulfate, 0.01 M ascorbic acid and 0.5% polyethylene glycol were extracted with an extraction ratio of 1:4 (w/v) for three minutes by using a blender. The purpose of study was to determine the optimum conditions for polyphenol oxidase extraction from potato and apple.